Brownmillerite‐type Ca2FeCoO5 as a Practicable Oxygen Evolution Reaction Catalyst. Issue 14 (11th July 2017) - Tsuji, Etsushi; Motohashi, Teruki; Noda, Hiroyuki; Kowalski, Damian; Aoki, Yoshitaka; Tanida, Hajime; Niikura, Junji; Koyama, Yukinori; Mori, Masahiro; Arai, Hajime; Ioroi, Tsutomu; Fujiwara, Naoko; et al.
Abstract: Invited for this month′s cover is the group of Prof. Dr. Hiroki Habazaki at Hokkaido University with their collaborators from Kanagawa University, Kyoto University, and the National Institute of Advanced Industrial Science and Technology. The image shows the oxygen evolution reaction on brownmillerite‐type Ca2 FeCoO5 categorized as an oxygen‐deficiency‐ordered perovskite in a basic solution. The Communication itself is available at10.1002/cssc.201700499 . Abstract : "Our discovery of the remarkable OER activity will stimulate researchers' renewed interest…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at10.1002/cssc.201700499 . View the Front Cover here:10.1002/cssc.201701191 .